Identification of upregulated genes under cold stress in cold-tolerant chickpea using the cDNA-AFLP approach. - Ali Dinari (Public Library of Science (PLoS), 2013)
Low temperature injury is one of the most significant causes of crop damage worldwide. Cold acclimatization processes improve the freezing tolerance of plants. To identify genes of potential importance for acclimatzation to the cold and to elucidate the pathways that regulate this process, global transcriptome expression of the chickpea (Cicer arietinum L), a species of legume, was analyzed using the cDNA-AFLP technique. In total, we generated 4800 transcript-derived fragments (TDFs) using cDNA-AFLP in conjunction with 256 primer combinations. We only considered those cDNA fragments that seemed to be up-regulated during cold acclimatization. Of these, 102 TDFs with differential expression patterns were excised from gels and re-amplified by PCR. Fifty-four fragments were then cloned and sequenced. BLAST search of the GenBank non-redundant (nr) sequence database demonstrated that 77 percent of the TDFs belonged to known sequences with putative functions related to metabolism (31), transport (10), signal transduction pathways (15) and transcription factors (21). The last group of expressed transcripts showed homology to genes of unknown function (22). To further analyze and validate our cDNA-AFLP experiments, the expression of 9 TDFs during cold acclimatzatiion was confirmed using real time RT-PCR. The results of this research show that cDNA-AFLP is a powerful technique for investigating the expression pattern of chickpea genes under low-temperature stress. Moreover, our findings will help both to elucidate the molecular basis of low-temperature effects on the chickpea genome and to identify those genes that could increase the cold tolerance of the chickpea plant.